Webinar Mewujudkan UMKM Unggul melalui Pendampingan Berbasis ISO 9001: Sinergi Dosen Lintas Ilmu dalam Kegiatan PKM - Ketut Witara (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
Usaha Mikro, Kecil, dan Menengah (UMKM)) are the backbone of Indonesia’s economy but still struggle with inconsistent product quality, weak managerial systems and limited competitiveness. This community‑engagement project aimed to strengthen MSME capabilities through ISO 9001:2015‑based quality management mentoring. An interactive webinar titled “Realising Excellent MSMEs through ISO 9001‑Based Assistance” was delivered by a multidisciplinary team of lecturers acting as trainers and facilitators. Training sessions combined conceptual lectures, implementation case studies and discussions on drafting SOPs, conducting internal audits and applying risk‑based thinking. Participants received a comprehensive package covering the rationale for quality management, the structure of clauses 4–10, and the step‑by‑step route to external certification. Post‑training feedback indicated improved understanding of how ISO 9001 can systematise processes, enhance efficiency and build market trust. The project demonstrates that knowledge‑driven academic–industry collaboration can accelerate MSMEs’ move “up the ladder” and make them more competitive. Follow‑up on‑site mentoring is recommended to ensure sustained adoption of ISO 9001 within participating enterprises.